Team Productivity and Team Work: Bibliometric Analysis - Ismawati Ismawati; Madziatul Churiyah (Jurnal Syntax Transformation, 2022)
It should be realized together that to develop Human Resources every organization has limitations. Therefore, it is necessary to involve other parties in the process of developing Human Resources. It is through this way that team productivity and teamwork are needed. The bibliometric literature method uses a systematic and detailed approach. This study aims to analyze the sources of literature related to keyword "team productivity "OR" team work "OR" team effectiveness "OR" team performance". In this study using bibliometric analysis published as many as 51 in journals or in proceedings and indexed in the scope of the time duration used 2017-2021, this provides an overview of the development of further research that will be used in companies, especially work teams in increasing productivity, team work, providing some information can be developed research with team work and team productivity.